Pengaruh Green Brand Image, Green Brand Trust, Green Brand Awareness dan Green Brand Satisfaction terhadap Purchase Intention pada Konsumen Air Mineral Merek Aqua - Rahmadhani, Annisa Vivit; Widodo, Arry (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The study analyzes how green brand image, green brand trust, green brand awareness and green brand satisfaction affect consumer purchase intentions for Aqua brand mineral water products in Boyolali, Central Java. This causal research uses 100 consumers as respondents. Data were collected using a questionnaire, then analyzed using multiple linear regression methods and partial and simultaneous hypothesis testing. Based on the research results obtained both partially and simultaneously, the four independent variables tested have a significant influence on the dependent variable. Based on the regression coefficient, green brand image has a dominant influence on purchase intention compared to other independent variables.